QoS Based web services selection using a Bi-Level model - Lakshmi, HN (International Journal of Computer Sciences and Engineering, 2025)
Service registries and web service engines are the main approaches for discovering web services. UDDI offers limited search functionalities which may return a huge number of irrelevant services. Often consumers may be unaware of precise keywords to retrieve the required services satisfactorily and may be looking for services capable of providing certain outputs. Another critical challenge in web service search and composition is the selection of web services, to be executed or to be composed, from the pool of matching services. Most of the current service selection proposals apply a weighted sum model (WSM) as an evaluation method for selection of services with the same functionality. In this paper, we propose a new system called Extended Service Registry (ESR) for extended and efficient service search and selection using an object relational database. ESR uses a bi-level service selection approach that selects the most appropriate web services from the pool of matching services that considers both the functional and non-functional requirements for service selection. The functional requirements are provided by the user as a set of input parameters provided for and output parameters desired from the web service. The user also provides a set of desired QoS values and the order of their preference for selection. The experimental results demonstrate the efficiency of service search in our Extended Service Registry (ESR) and the variety of user queries supported.